ترشيد تكاليف الاستثمار في تكنولوجيا المعلومات بتطبيق أسلوبي محاسبة النشاط ودورة حياة المنتج - رحومة، نوري أبو لقاسم; رحومة، عبدالسلام محمد عبيد Rahoma, Abdelsalam Mohamed Abaid (جامعة الزيتونة - كلية الإقتصاد والعلوم السياسية - سوق الأحد, 2016)
Became the tools of information technology (hardware, equipment, software, and database), an influential element in the economic units in general as they provided these tools of appropriate information and quick help economic units in the completion of its work efficiently and effectively and in a timely manner, and based the main objective of this study is to analyze the various aspectslnvestment in information technology ('intranets), and searches that match the method of accounting on the basis of ABC activity and the life cycle of the product/ service in order to increase the competitiveness of businesses.
أصبحت أدوات تكنولوجيا المعلومات (الأجهزة والمعدات، والبرمجيات، وقاعدة البيانات) عنصرا مؤثرا في الوحدات الاقتصادية بشكل عام نظرا لما توفره هذه الأدوات من معلومات ملائمة وسريعة تساعد الوحدات الاقتصادية في إنجاز أعمالها بكفاءة وفاعلية وفي الوقت المناسب، ويرتكز الهدف الرئيسي لهذه الدراسة في تحليل الجوانب المختلفة للاستثمار في تكنولوجيا المعلومات (الشبكات الداخلية)، وبحث تطابق أسلوب المحاسبة علي أساس النشاط ABC ودورة حياة (المنتج / الخدمة)، بهدف زيادة القدرات التنافسية في منشآت الأعمال.
Keywords: تكنولوجيا المعلومات -- دورة حياة المنتج -- محاسبة التكاليف